DEVELOPING TEST FOR READING REPORT TEXT BASED ON TWO-TIER MULTIPLE CHOICES TEST FOR JUNIOR HIGH SCHOOL STUDENTS - Lampita Kristianti Simamora; Anni Holila Pulungan (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
This study aims to develop a test for reading report text based on the Two-Tier Multiple Choices test for Junior High school students in SMP Negeri 3 Dooksanggul. The Two-Tier Multiple Choices Test was developed by using Research and Development (R&D) method proposed by Borg and Gall (2007), which has been modified by Sugyono (2016). It consists of six steps: gathering data and information, analyzing data, developing material, validating by experts, revising the product, and developing the final product. The test instrument developed was a twolevel multiple choice test consisting of multiple-choice questions and a choice of reasons totaling 30 questions. The validator assessment sheet consists of three aspects, namely material, construction, and language, with 12 assessment indicators and is analyzed using the Content Validity Index (CVI). The first draft was revised based on validation results and experts' comments to develop a better test instrument. The developed reading test validated the Content Validity Index (CVI) score was 1.00. It concluded that the instrument test was categorized as "Very Good."